The Effect of Earnings Management on Corporate Social Responsibility with Corporate Governance as Moderator - Iskandar Itan; Mardianto; Rizka Putri Pratama (Accounting Department, Faculty of Business and Management, Universitas Internasional Batam, 2026)
Purpose - this study examines the nexus between CSR, Accrual Earning Management and Real Earning Management and whether Corporate Governance can moderate that connection. Research Method - this research uses a quantitative approach with the STATA application. Tables such as descriptive statistics and regression analysis will be presented to achieve the research objectives. This analysis relies on longitudinal data from companies listed on the Indonesia Stock Exchange (IDX), 299 companies from the period 2019 - 2023. Findings – The results of this paper show that both Accrual Earning Management and Real Earning Management are positively associated with Corporate Social Responsibility. We also found that Corporate Governance can limit the opportunistic activities of managers in manipulating earnings.